Financial Constraints and Corporate Environmental Policies - Xu, Qiping; Kim, Taehyun (Review of Financial Studies, 2022)
Abstract This paper documents evidence that financial constraints increase firms’ toxic emissions given that firms actively trade off abatement costs against potential legal liabilities. Exploring three quasi-natural experiments in which firms’ financial resources are likely exogenously affected, we find that relaxing financial constraints reduces U.S. public firms’ toxic releases. The effects of financial constraints on toxic releases are amplified when regulatory enforcement and external monitoring weaken. Overall, our evidence highlights the real effects of financial constraints in the form of environmental pollution, which is a costly negative externality imposed on society and public health.